2011
DOI: 10.1037/a0020547
|View full text |Cite
|
Sign up to set email alerts
|

To whom the play signal is directed: A study of headshaking in black-handed spider monkeys (Ateles geoffroyi).

Abstract: Spider monkeys shake their heads so as to facilitate amicable social contact. This occurs frequently during vigorous play fighting, and so is common during the juvenile period. Occasionally, juvenile spider monkeys use headshakes during nonsocial locomotor play. In this study, head shaking in early infancy and in adulthood was studied in a captive troop of spider monkeys, with a total of 8 infants studied from shortly after birth to just before weaning. Three hypotheses to account for these nonsocial headshake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
(60 reference statements)
1
22
0
Order By: Relevance
“…Playful attacks typically decline throughout puberty [42,43], suggesting that ISO rats may remain in an immature stage of social development. Play-like social interactions that vary too far from the expected behaviors are no longer considered playful [44] and may instead be interpreted as aggressive, thus provoking aggression from the experimental rats. Regardless of whether the interactions are agonistic or simply age-inappropriate, rats engaging in high levels of these behaviors may model social ineptness in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Playful attacks typically decline throughout puberty [42,43], suggesting that ISO rats may remain in an immature stage of social development. Play-like social interactions that vary too far from the expected behaviors are no longer considered playful [44] and may instead be interpreted as aggressive, thus provoking aggression from the experimental rats. Regardless of whether the interactions are agonistic or simply age-inappropriate, rats engaging in high levels of these behaviors may model social ineptness in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Playful attacks decline throughout puberty (Panksepp, 1981), suggesting that PSI rats may be “stuck” in an immature stage of social development, and this may be unexpected by the stimulus rat. Pellis and Pellis (2011) have suggested that play-like social interactions that vary too far from the expected behaviors are no longer considered playful, so that conspecifics avoid interactions with the individuals engaging in these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pellis and Pellis [77] demonstrated that the role of play signals in self-regulating emotional state is also present in spider monkeys. Yet, there are some greater cognitive overlap and developmental similarities between Pan and Homo than between either and other primate species.…”
Section: Discussionmentioning
confidence: 99%